(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the present study was to determinate the biologically active substance in 95% ethanol and subsequent water extracts from Bulgarian comfrey (Symphylus officinale L.) roots and to evaluate their antioxidant potential. The antioxidant activity was evaluated by several reliable methods such as DPPH-, ABTS-, FRAP-, CUPRAC-, ORAC and HORAC-assays, as well as the total phenolic content. In addition, the total organic, fructose and sugar content were determined by spectrophotomeric and HPLC-RID methods. The level of fructans in ethanol extracts was 25.2 g/100g dry weight, as nystose and 1-kestose were only 0.1g/100g dry weight, and 0.3g/100g dry weight, respectively. The absence of fructooligosacharides in water extracts after the ethanol pretreatment was established. Inulin content was evaluated to be 25.2 g/100 g dry weight. In addition, total uronic content was established to be 2.0 g/100 g dw as its level dominated in water extracts – 1.7 g/100 g dw, respectively. The metabolite profile of roots revealed their potential application as radical scavengers due to the presence of polyphenols. Phenolic acids (neochlorogenic, p-coumaric and gallic acids) and flavonoids (quecetin, myrecitin and naringin) were the dominant polyphenols in comfrey extracts. Therefore, the root extracts of Symphylus officinale L. could be assumed as a rich source of biologically active substance, in particular dietary fiber with potential prebiotic effect, due to the presence of polysaccharide inulin and fructooligosacharides.